The Influence of Load on Dry and Tribocorrosive Sliding of AISI 4330 and 15-5PH against Cast Iron. Issue 5 (3rd September 2021) - Woodward, Ronnie G.; Toumpis, Athanasios; Galloway, Alexander; Sillars, Fiona; Marrocco, Tiziana; Olasolo, Maider; Wallace, Andrew
Abstract: Environmental conditions, testing variables, and material properties significantly influence the sliding wear behavior of all tribosystems. Such parameters affect the mechanism of wear occurring, govern how the wear scar will be categorized, and control whether transitions occur throughout the test. The present study investigated this through sliding wear tests of AISI 4330, 15-5PH, and heat-treated cast iron in the dry and NaCl regime. Loads of 2, 4, and 6 kg were applied to the cast iron pin in both regimes, with the volume loss results, wear scar morphology, and microstructural evolution analyzed. It was found that the AISI 4330 and 15-5PH discs produced higher volume losses in the dry regime than in the NaCl regime, indicating that the solution had a beneficial effect rather than a detrimental effect versus the dry tribosystem. Beneficial oxidative wear allowed for AISI 4330 to lose less than 15-5PH in the dry regime, with their respective cast iron pins following the same result. Microstructurally, the 15-5PH wear scar cross sections exhibited a mechanically mixed surface layer of refined material mixed with oxides above a layer of grains distorted in the direction of sliding. This highlighted the significant difference between the wear of 15-5PH and AISI 4330, because the latter did not exhibit any areas of interest.